SEBAB-SEBAB CERAI GUGAT DI PENGADILAN AGAMA CIAMIS TAHUN 2017 - Yahya Yahya; Ahmad Nabil Atoillah; Ayi Ishak Sholih Muchtar (Istinbath | Jurnal Penelitian Hukum Islam, 2019)
Divorce is the last solution that can be taken by a husband and wife in ending a marriage bond after holding peace or mediation to the maximum can be done at the wishes of the husband or the wife's request. Divorce made at the request of the wife is called a divorce. The purpose of divorce is the request of the wife to her husband to divorce (release) her from a marriage bond accompanied by iwadh in the form of money or goods to the husband in return for the imposition of divorce divorce. The imposition of divorce is as giving equal rights for women to break away from marital ties which are considered to have no benefit, and realize that wives also have the same rights to end marriages. This means that in certain situations a wife who is very tormented due to her husband has the right to sue for divorce with iwadh. In domestic life, even though at first husband and wife are full of affection as if it will not fade, it can even disappear with hatred. If hatred has come and husband and wife do not sincerely seek a way out and restore their love, it will negatively affect their offspring. Therefore, efforts to restore love are something that needs to be done. It is true that love is turned into hatred, but it also needs to be remembered that hatred can then return to love. The case of divorce in the Ciamis Religious Court in 2017 is very high according to information from the court